Optical encryption for visible light communication based on temporal ghost imaging with a micro-LED. (November 2020) - Wang, Yupeng; Chen, Honglan; Jiang, Wenjie; Li, Xianye; Chen, Xinwei; Meng, Xiangfeng; Tian, Pengfei; Sun, Baoqing
Highlights: Developing a completely new scheme for optical encryption in visible light communication. Application of dual encryption of digital algorithm (temporal ghost imaging) and physical hardware (micro-LED). Realizing optical communication of error-free, high robustness and high security. Opening up a new application scenario for temporal ghost imaging. Abstract: As the great application potential of visible light communication (VLC) in the next generation communication after 5G, study of the transmission security in VLC is high desirable with the rapid growth of wireless network traffic. In this paper, an optical encryption scheme for VLC is proposed based on temporal ghost imaging (TGI) with a micro-light-emitting diode (micro-LED). The target temporal signal is digitally encrypted by a sequence of randomized orthogonal secret key. The micro-LED working at 4 Gbps (over 20 times higher than its bandwidth ~160 MHz) physically encrypts the information in a non-invertible way due to the severe transmission distortion. According to TGI theory, correlation calculation between the integration value of received distorted signal and the secret key can realize the decryption process without error. The integrated encryption of digital algorithm and physical hardware property guarantee the security of this method. We experimentally demonstrate the system can resist attack of up to 40% occlusion or 80% Gaussian noise and obtain error-free signal.